A method for determining the sulfur content in antimony ore by high frequency infrared absorption method

CN122882372APending Publication Date: 2026-10-09CHINA GEOLOGICAL SURVEY URUMQI NATURAL RESOURCES COMPREHENSIVE SURVEY CENT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611205255.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种高频红外吸收法测定锑矿石中硫含量的方法,本发明针对性优化测定参数,适配锑矿石的独特性,确定了最佳测定条件,从根本上解决了现有参数适配性差的问题,保障了测定结果的准确性

Benefits of technology

1)兼顾测定效率与环保性,适配行业实际需求:相较于燃烧碘量法、硫酸重量法等传统方法,本发明依托高频红外碳硫仪的技术优势,大幅缩短分析时长,减少化学试剂的使用,无有毒有害废液产生,既提升了锑矿勘查开发中硫含量的检测效率,又规避了传统方法的环境污染与操作人员安全隐患问题,符合现代地质检测的绿色、高效发展要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122882372A_ABST
    Figure CN122882372A_ABST
Patent Text Reader

Abstract

The application provides a method for determining the sulfur content in antimony ore by high-frequency infrared absorption method, and belongs to the technical field of analysis and detection. The application establishes a standardized determination method for the sulfur content in antimony ore based on a high-frequency infrared carbon-sulfur instrument. The core problem of the method is that the high-frequency combustion of the complex antimony ore containing a large amount of sulfide and oxide of antimony is easy to form a low-melting-point melt to wrap the sample, resulting in incomplete release of sulfur. The application optimizes key influencing factors such as the sample weight, the selection and proportioning of flux, and the analysis time, and determines the optimal determination conditions of the antimony ore, fundamentally solves the problem of poor adaptability of the existing parameters, and guarantees the completeness of sulfur release and the accuracy of the determination results. Further, the application further guarantees the accuracy of the determination results by optimizing key influencing factors such as the crucible treatment and sample drying.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of analytical testing technology, specifically relating to a method for determining the sulfur content in antimony ore using high-frequency infrared absorption. Background Technology

[0002] Sulfur is a major harmful associated element in antimony ore, and its content is an important indicator for classifying antimony ore grades, distinguishing between rich and poor ore, and identifying difficult-to-process ore. The reduced comprehensive utilization value of high-sulfur antimony ore directly impacts mining planning and resource assessment.

[0003] Traditional methods for detecting elements in antimony ore, such as combustion iodometric titration, sulfuric acid gravimetric method, and potentiometric titration, are generally complex in operation, have long analysis cycles, require large amounts of chemical reagents, and are prone to generating toxic and harmful waste liquids, posing safety hazards to operators. These methods cannot meet the needs of rapid and environmentally friendly testing in antimony ore geological exploration and mineral development.

[0004] Existing technologies use high-frequency infrared carbon-sulfur analyzers to determine the sulfur content of antimony-based materials / other ores. For example, one existing technology uses high-frequency infrared carbon-sulfur analyzers to determine the sulfur content in antimony concentrates. However, considering the complex matrix characteristics of antimony ore (containing a large amount of antimony sulfides / oxides, and easily forming melts), the accuracy and precision of this method cannot meet the quality requirements of geological and mineral experiments. Furthermore, the matrix composition of antimony concentrates differs significantly from that of antimony ore, making the method unsuitable for direct application. Another existing technology determines trace amounts of sulfur in metallic antimony. However, metallic antimony has a single matrix, which differs significantly from the matrix characteristics of antimony ore (which contains multiple minerals and has a complex composition), making this method also unsuitable for direct application.

[0005] In summary, traditional methods cannot meet the needs of rapid and environmentally friendly testing. Currently, there is no high-frequency infrared carbon-sulfur analyzer for determining sulfur content in antimony ore, and the high-frequency infrared absorption method cannot be directly applied to the determination of sulfur content in antimony ore. Summary of the Invention

[0006] The purpose of this invention is to provide a method for determining the sulfur content in antimony ore using high-frequency infrared absorption. This invention specifically optimizes the measurement parameters to suit the unique characteristics of antimony ore, determines the optimal measurement conditions, fundamentally solves the problem of poor adaptability of existing parameters, and ensures the accuracy of the measurement results.

[0007] To achieve the objectives of this invention, the following technical solutions are provided: A method for determining the sulfur content in antimony ore using high-frequency infrared absorption spectrometry includes the following steps: S1. Establishing the working curve: Antimony ore standard material was measured using a high-frequency infrared carbon-sulfur analyzer, and the instrument infrared response value of the antimony ore standard material was recorded. With the sulfur content standard value of the antimony ore standard material as the abscissa (x) and the instrument infrared response value as the ordinate (y), a linear calibration curve was fitted using a multi-point calibration method to obtain the sulfur content determination working curve. The working curve is y = 0.9996x + 0.023, with a correlation coefficient R0. 2 =0.9995; S2. Sulfur content detection in antimony ore samples: Antimony ore samples are graded and weighed according to their sulfur content, and then dried to obtain antimony ore samples to be tested. The antimony ore sample to be tested and the flux are mixed and placed in a high-frequency infrared carbon-sulfur analyzer. The test program is started, and the sulfur content of the antimony ore sample is calculated and output according to the working curve. The flux is iron filings, tungsten granules, and tin granules; the mass ratio of the iron filings, tungsten granules, and tin granules is 0.48~0.52:1.4~1.6:0.48~0.52. The graded sampling includes: antimony ore with a sulfur content of 1.0~10wt%, with a sample weight of 50mg; antimony ore with a sulfur content of ≈1wt%, with a sample weight of 100mg; and antimony ore with a sulfur content of 10.0~20.0wt%, with a sample weight of 20mg.

[0008] Preferably, the mixing in step S2 is carried out in a crucible; the crucible is pretreated before use; the pretreatment temperature is 1180~1220℃.

[0009] Preferably, the operating parameters of the high-frequency infrared carbon-sulfur analyzer are: output power of 3.4~3.6 kW; input current of 19~21 A; and analytical gas flow rate of 4 L·min. -1 Oxygen flow rate is 1.5~2.0 L·min -1 The gas pressure is: oxygen output pressure 0.6 MPa, oxygen input pressure 0.30~0.50 MPa, total oxygen pressure 0.18 MPa, and analysis pressure 0.08 MPa. The time parameters are: rinsing time 30 s, delay time 3 s, desorption time 60 s, and combustion time 40~50 s.

[0010] Preferably, in step S2, the antimony ore sample to be tested and the flux are mixed by adding iron filings, tungsten particles and tin particles to the antimony ore sample in sequence without stirring.

[0011] Preferably, the tungsten particles have a particle size of 0.380 mm; the tin particles have a particle size of 280~830 μm.

[0012] Preferably, the particle size of the antimony ore sample is ≤200 mesh.

[0013] Preferably, the total mass percentage of antimony oxides in the antimony ore sample is 5.0~70.0 wt%.

[0014] Preferably, the drying temperature in step S2 is 60~80℃ and the time is 1~2h.

[0015] This invention provides a method for determining the sulfur content in antimony ore using high-frequency infrared absorption spectroscopy. Based on a high-frequency infrared carbon-sulfur analyzer, this invention establishes a standardized method for determining the sulfur content in antimony ore. The specific determination principle is as follows: Based on the principle of infrared absorption spectroscopy, utilizing the characteristic strong absorption band of sulfur dioxide (SO2) at 7.35 μm, the antimony ore is burned at high temperature, completely converting all forms of sulfur in the sample into SO2 gas. Using high-purity oxygen as the carrier gas, SO2 is introduced into the infrared detection system. By measuring the change in the characteristic absorption intensity of SO2, combined with the calibration curve prepared from the national standard material for antimony ore, the sulfur content in the antimony ore is indirectly and quantitatively calculated. This provides a unified and reliable detection technical specification for this field and has pioneering technical value.

[0016] Furthermore, this invention addresses the core issue of incomplete sulfur release caused by the complex composition of antimony ore, which contains large amounts of antimony sulfides and oxides, and the tendency for high-frequency combustion to form a low-melting-point melt that encapsulates the sample. It systematically explores and optimizes key influencing factors such as sample weight, flux selection and ratio, analysis, and combustion time, determining the optimal measurement conditions. This fundamentally solves the problem of poor parameter adaptability in existing methods, ensuring the completeness of sulfur release and the accuracy of the measurement results. Furthermore, this invention further guarantees the accuracy of the measurement results by optimizing key influencing factors such as crucible treatment and sample drying.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1) Balancing measurement efficiency and environmental friendliness, adapting to actual industry needs: Compared with traditional methods such as combustion iodometric titration and sulfuric acid gravimetric method, this invention relies on the technical advantages of high-frequency infrared carbon-sulfur analyzer to significantly shorten analysis time, reduce the use of chemical reagents, and generate no toxic or harmful waste liquid. It not only improves the detection efficiency of sulfur content in antimony ore exploration and development, but also avoids the environmental pollution and safety hazards to operators caused by traditional methods, which meets the requirements of green and efficient development of modern geological testing.

[0018] 2) The test results are accurate and reliable, meeting the laboratory quality standards: The calibration curve is prepared using the national standard material for antimony ore. It has been verified that the relative error of the test results of this invention is less than 1.96%, and the relative standard deviation is less than 1.35%. The precision is good and the accuracy is high, which fully meets the requirements of the quality management specifications for geological and mineral laboratory testing, and can be promoted and used as a routine laboratory testing method.

[0019] 3) The parameter design is scientific and reasonable, taking into account both practicality and economy: In the optimization of parameters such as flux selection and ratio, analysis time, the fluxing effect and combustion completeness are guaranteed, while avoiding problems such as excessive dilution of samples by flux and excessive analysis time increasing costs. At the same time, the samples are dried in an oven, eliminating the need for complex heating equipment, making the operation simple, reducing the detection cost and operation threshold, and facilitating its widespread application in grassroots geological testing laboratories.

[0020] 4) The method has strong applicability and expansion value: The optimized ideas and determination parameters of this invention for antimony ore can provide important methodological reference for the infrared determination of sulfur content in other refractory sulfide matrix ores containing antimony, arsenic, bismuth, and lead, which are prone to forming low-melting-point molten inclusions. It has good technical expansion and reference value. Attached Figure Description

[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0022] Figure 1 The results show the effect of blank treatment before and after crucible preparation on the measurement results; Figures 2-5 The results show the effect of the degree of sample drying on the determination of sulfur content; Figures 6-9 The results show the effect of different sample masses on the determination of sulfur content in four standard substances. Detailed Implementation

[0023] This invention provides a method for determining the sulfur content in antimony ore using high-frequency infrared absorption, comprising the following steps: S1. Establishing the working curve: Antimony ore standard material was measured using a high-frequency infrared carbon-sulfur analyzer, and the instrument infrared response value of the antimony ore standard material was recorded. With the sulfur content standard value of the antimony ore standard material as the abscissa (x) and the instrument infrared response value as the ordinate (y), a linear calibration curve was fitted using a multi-point calibration method to obtain the sulfur content determination working curve. The working curve is y = 0.9996x + 0.023, with a correlation coefficient R0. 2 =0.9995; S2. Sulfur content detection in antimony ore samples: Antimony ore samples are graded and weighed according to their sulfur content, and then dried to obtain antimony ore samples to be tested. The antimony ore sample to be tested and the flux are mixed and placed in a high-frequency infrared carbon-sulfur analyzer. The test program is started, and the sulfur content of the antimony ore sample is calculated and output according to the working curve. The flux is iron filings, tungsten granules, and tin granules; the mass ratio of the iron filings, tungsten granules, and tin granules is 0.48~0.52:1.4~1.6:0.48~0.52. The graded sampling includes: antimony ore with a sulfur content of 1.0~10wt%, with a sample weight of 50mg; antimony ore with a sulfur content of ≈1wt%, with a sample weight of 100mg; and antimony ore with a sulfur content of 10~20wt%, with a sample weight of 20mg.

[0024] Unless otherwise specified, all reagents used in this invention are commercially available products well known to those skilled in the art.

[0025] In this invention, the antimony ore standard materials can specifically be GBW07279, GBW07280, GBW(E)070168, GBW07174, GBW07175 and GBW07176.

[0026] In this invention, a high-frequency infrared carbon-sulfur analyzer is used to determine the antimony ore standard material. The specific steps are as follows: Samples are weighed according to the sulfur content in antimony ore standard materials, and then dried to obtain the standard samples to be tested. The standard sample to be tested and the flux are mixed and placed in a high-frequency infrared carbon-sulfur analyzer. The test program is started and the instrument infrared response value of the antimony ore standard material is recorded.

[0027] In this invention, the graded weighing of the antimony ore standard material includes: antimony ore standard material with a sulfur content of 1.0~10wt%, weighing 50mg; antimony ore standard material with a sulfur content of ≈1wt% (≤1wt%), weighing 100mg; and antimony ore standard material with a sulfur content of 10.0~20.0wt%, weighing 20mg.

[0028] In this invention, six samples of each antimony ore standard material are prepared in parallel for subsequent parallel processing and determination.

[0029] In this invention, the drying temperature is 60~80℃ and the time is 1~2h.

[0030] In this invention, the standard sample to be tested and the flux are mixed in a crucible; the crucible is pretreated before use; the pretreatment temperature is 1180~1220℃, and in a specific embodiment it can be 1200℃.

[0031] In this invention, the operating parameters for the high-frequency infrared carbon-sulfur analyzer to determine antimony ore standard materials are as follows: output power of 3.4~3.6kW; input current of 19~21A; and analytical gas flow rate of 4 L·min. -1 Oxygen flow rate is 1.5~2.0 L / min. -1 The gas pressure is 0.6 MPa for oxygen output, 0.30-0.50 MPa for oxygen input, 0.18 MPa for total oxygen pressure, and 0.08 MPa for analysis pressure. The time parameters are: rinsing time 30 s, delay time 3 s, desorption time 60 s, and combustion time 40-50 s, which can be 45 s in a specific embodiment.

[0032] In this invention, the mixing method of the test standard sample and flux is as follows: iron filings, tungsten particles, and tin particles are added sequentially to the test standard sample without stirring. In this invention, the flux consists of iron filings, tungsten particles, and tin particles; the mass ratio of the iron filings, tungsten particles, and tin particles is 0.48~0.52:1.4~1.6:0.48~0.52, and in a specific embodiment, it can be 0.5:1.5:0.5; the particle size of the tungsten particles is 0.380 mm; and the particle size of the tin particles is 280~830 μm.

[0033] In this invention, antimony ore typically generates Sb₂O₃ and Sb₂S₃ during combustion, forming a low-melting-point liquid phase (≈500℃) that instantly encapsulates the sample, creating a "sealed shell" that prevents oxygen from entering and sulfur from being released. This invention addresses the problem of melt encapsulation from three angles through the synergistic effect of a ternary composite flux: iron filings improve the efficiency of high-frequency induction heating, rapidly increasing furnace temperature and breaking the conditions for low-melting-point melt formation, thus preventing premature melt encapsulation of the sample; tungsten particles form a loose, porous framework structure, physically supporting the molten pool, preventing antimony melt agglomeration and sample encapsulation, ensuring continuous oxygen penetration and complete combustion; tin particles significantly reduce slag viscosity and improve melt flowability, allowing the Sb oxide melt to spread rapidly without agglomeration, ensuring complete sulfur release as SO₂. The synergistic effect of these three components provides advantages such as rapid heating, no agglomeration, good permeability, and smooth flow, fundamentally overcoming the technical defect of low-melting-point melt encapsulation during high-frequency combustion of antimony ore.

[0034] Secondly, this invention controls the mixing sequence of the standard sample and flux to be tested as follows: iron filings, tungsten particles, and tin particles are added to the standard sample in sequence without stirring; that is, they are layered and then electrically melted and burned. After mixing, this invention forms a layered, non-stirred structure consisting of a crucible bottom layer, an antimony ore sample layer, an iron filings layer, a tungsten particle layer, and a small amount of tin particles on the surface. This structure has the following advantages: 1) The iron filings adhere closely to the antimony ore sample, generating eddy current heat immediately, which rapidly heats up the sample in the early stages to decompose antimony sulfide, avoiding localized low temperatures and incomplete decomposition of antimony sulfide; 2) The tungsten particle layer releases a large amount of heat, forming a high-temperature melting pool, isolating air, preventing premature volatilization of antimony and sulfur, and inhibiting low-temperature oxidation of Sb2S3 and premature escape of SO2; 3) The tin particles are on the outermost layer, slowly sinking after melting, improving the slag throughout the process, preventing premature reaction with the sample and splashing, and inhibiting Sb volatilization; 4) The mixing method of this invention results in stable combustion, symmetrical integral peak shape, small relative standard deviation (RSD) of parallel samples, and stable sulfur results. Compared to existing technologies that use co-mixing: 1) Tungsten particles have high density, iron filings are flaky, and tin particles are granular. After stirring, tungsten particles sink while iron and tin float on the surface, and the mineral sample is dispersed in the flux gaps, resulting in insufficient initial heating; 2) Tin particles come into full contact with fine antimony sulfide particles, which can easily cause localized and violent reactions at low temperatures, resulting in splashing. The loss of trace amounts (e.g., 20 mg) of sample is particularly severe; 3) Antimony is highly volatile. After mixing, there is no tungsten layer to isolate it, and some Sb and SO2 escape prematurely in the early stage of heating, resulting in lower sulfur determination results and poor repeatability; 4) The slag has poor formation and easily encapsulates undecomposed mineral particles, causing SO2 release tailing and drifting of the integration results.

[0035] In this invention, the particle size of the antimony ore sample is ≤200 mesh.

[0036] After obtaining the sulfur content determination working curve, the present invention detects the sulfur content of antimony ore by: weighing samples according to the sulfur content in the antimony ore, drying them to obtain the sample to be tested; mixing the sample to be tested with flux and placing it in a high-frequency infrared carbon-sulfur analyzer, starting the determination program, and calculating and outputting the sulfur content determination value of the antimony ore sample according to the working curve.

[0037] In this invention, the grading and weighing of the antimony ore sample to be tested is consistent with that of the antimony ore standard material; the determination procedure of the antimony ore sample using the high-frequency infrared carbon-sulfur analyzer is consistent with that of the antimony ore standard material, and will not be repeated here.

[0038] In this invention, the mixing method of the antimony ore sample to be tested and the flux is the same as the mixing method of the standard sample to be tested and the flux.

[0039] In this invention, the antimony ore includes one or more of primary antimony ore, antimony oxide ore, and antimony sulfide ore; the mass fraction of sulfur in the antimony ore is 1.0% to 20.0 wt%; the total mass percentage of antimony oxides is 5.0% to 70.0 wt%, and the antimony oxides include Sb2O3, Sb2O4, and Sb2O5.

[0040] To further illustrate the present invention, the method for determining the sulfur content in antimony ore by high-frequency infrared absorption method provided by the present invention will be described in detail below with reference to the accompanying drawings and embodiments, but these should not be construed as limiting the scope of protection of the present invention.

[0041] The parameters of the instruments and reagents used in the following embodiments of the present invention are as follows: High-frequency infrared carbon and sulfur analyzer: KR-205 model; Ceramic crucible: Ф25mm, for use with a high-frequency infrared carbon-sulfur analyzer; Electronic balance: LCPA225D type (accuracy ≥ 0.0001g); Muffle furnace / tube resistance furnace: Temperature control range 0~1300℃, temperature control accuracy ±5℃; Dryer: Built-in color-changing silica gel desiccant; Ore grinding equipment: grinds antimony ore to ≤200 mesh.

[0042] Pure iron filings flux: w(Fe)≥99.8%, w(S)<0.0005%, free from sulfur impurities; Tungsten granular flux: particle size 0.380 mm, w(W) ≥ 99.95%, w(S) ≤ 0.0003%; Tin granules: 280~830 μm, Deyang Kerui Instrument Equipment Factory; High-purity oxygen: purity ≥ 99.99%, used as combustion-supporting gas and SO2 carrier gas; Antimony ore composition analysis standard references: GBW07279, GBW07280, GBW07174, and GBW07176 were selected, with sulfur content gradients covering 1.0% to 20%; Color-changing silica gel: analytical grade.

[0043] Example 1 (I) Sample and crucible pretreatment 1. High-temperature pretreatment of ceramic crucibles Place the special ceramic crucibles in a muffle furnace, maintaining a gap (≥5mm) between crucibles to ensure sufficient air contact; heat the muffle furnace to 1200℃ and ignite at high temperature for 2 hours to thoroughly remove moisture, trace sulfur, and volatile impurities from the crucibles; after ignition, turn off the muffle furnace and allow the crucibles to cool naturally to room temperature (20~25℃), then quickly remove them and seal them in a desiccator for storage; the pretreated crucibles should be used within 24 hours to avoid prolonged exposure to air, which could lead to moisture absorption and impurity adsorption, resulting in an increase in blank values.

[0044] 2. Pretreatment of antimony ore samples The raw antimony ore is ground to a particle size of ≤200 mesh using grinding equipment; Take an appropriate amount of the ground antimony ore sample and dry it at 80℃ for 2 hours; seal the dried sample for storage to prevent it from absorbing moisture again.

[0045] (II) Sample Weighing and Flux Addition Using an electronic balance with an accuracy of 0.0001 g, a graded weighing strategy was established for antimony ore samples with different sulfur contents. Specifically, when the sulfur content of the sample is in the range of 1.0% to 10%, a sample weight of 50 mg is used, which balances sample representativeness and combustion conversion efficiency, resulting in stable and reliable measurement results. When the sulfur content of the sample is approximately 1 wt%, the weight is appropriately increased to 100 mg, which effectively reduces relative error and improves measurement precision. When the sulfur content of the sample is in the range of 10.0 wt% to 20.0 wt%, a weight of 20 mg is used, which avoids problems such as excessive combustion and splashing, unstable sulfur release, and exceeding the instrument's measurement range due to excessive sample weight, ensuring accurate detection results.

[0046] The weighed sample was placed in a ceramic crucible that had been pretreated at 1200℃ and then cooled. The crucible's side wall was gently tapped to ensure even distribution of the sample at the bottom, preventing accumulation. 0.5g of pure iron filings flux, 1.5g of tungsten granules flux, and 0.5g of tin granules were added sequentially to the crucible. The relative error in flux weighing was ≤±0.005g. The crucible was gently shaken to ensure the pure iron filings, tungsten granules, and tin granules were evenly distributed among the antimony ore sample in layers, guaranteeing sufficient contact between the flux and the sample during combustion. The mass ratio of sample to flux was antimony ore sample : pure iron filings : tungsten granules : tin granules = graded sample : 0.50g : 1.5g : 0.50g.

[0047] (III) Setting the Optimal Operating Parameters of the Instrument The high-frequency infrared carbon-sulfur analyzer should be adjusted to the following operating parameters. During the measurement process, the parameters should be kept stable. The core parameters can be fine-tuned within a reasonable range, as detailed below: Output power: 3.5kW; Input current: 20A; Analytical gas flow rate: 4L·min -1 (Fixed value); Oxygen flow rate: 1.5~2.0 L·min -1Gas pressure: Oxygen output pressure 0.6MPa, oxygen input pressure 0.30~0.50MPa, total oxygen pressure 0.18MPa, analysis pressure 0.08MPa; Time parameters: flushing time 30s, delay time 3s, desorption time 60s, combustion (analysis) time 45s (adjustable range 40~50s).

[0048] (iv) Establishment of calibration curves National standard materials GBW07279, GBW07280, GBW07174, and GBW07176, which cover a sulfur content gradient of 1.0% to 20%, were selected. Sample pretreatment, weighing, and flux addition were completed according to steps (I) to (II) of this embodiment. Six samples were prepared in parallel for each standard material. According to the instrument operating parameters set in this scheme (III), the prepared standard substance samples were sequentially placed into the combustion furnace of the high-frequency infrared carbon-sulfur analyzer for measurement, and the instrument infrared response value of each sample was recorded. The average response value of 6 parallel measurements of each standard substance was calculated. With the standard value of sulfur content (%) of the standard substance as the abscissa (x) and the average instrument response value as the ordinate (y), a linear calibration curve was fitted using the multi-point calibration method to obtain the regression equation y=ax+b and the linear correlation coefficient R. 2 Requires R 2 ≥0.999, to ensure good linearity of the curve; (V) Sample Measurement and Result Calculation The prepared antimony ore sample (sample + flux) was placed in the combustion furnace of the high-frequency infrared carbon-sulfur analyzer. The furnace door was closed, and the automatic measurement program was started according to the preset optimal operating parameters (step three). The instrument automatically completed high-frequency combustion, SO2 gas acquisition, infrared light intensity detection, and response value recording, based on the built-in calibration curve (y=0.9996x+0.023, correlation coefficient R). 2 =0.9995), automatically calculate and output the sulfur content (%) of the sample; each antimony ore sample is measured in parallel 3 times, and the arithmetic mean of the 3 measurements is taken as the final sulfur content result of the sample; the relative standard deviation (RSD) of the measurement results is ≤1.35%, which meets the requirements of the quality management specifications for geological and mineral laboratories.

[0049] (vi) Blank test and quality control 1. Blank test For each batch of sample testing (≤20 samples), a blank test must be performed simultaneously: take the same amount of pure iron filings flux (0.5g), tungsten granules flux (1.5g), and tin granules (0.5g) as the sample test, place them in a ceramic crucible pretreated at 1200℃, and perform the test according to the steps in this scheme (VII), and record the blank value; the blank value should be ≤0.003%. If the blank value exceeds the standard, immediately re-pretreat the crucible and replace the flux, and repeat the sample test.

[0050] 2. Accuracy and Precision Verification Precision: Two national standard reference materials of antimony ore with low and medium sulfur contents were selected, and the results were measured in parallel for 6 times according to this scheme. The relative standard deviation (RSD) of the measurement results was calculated. RSD < 1.35%; Accuracy: Using the sulfur content of the national standard reference material for antimony ore as the true value, the relative error (RE) of the determination results by this method is calculated, and RE < 1.96%; All test results must meet the relevant requirements of the "Geological and Mineral Laboratory Testing Quality Management Standard" in order to be considered as valid results.

[0051] Example 2 The effect of crucible treatment method on measurement results In this embodiment, the crucibles were divided into two groups. One group of crucibles was not subjected to high-temperature treatment, while the other group was calcined in a muffle furnace at 1200℃ for 2 hours (with gaps maintained between the crucibles to ensure full contact with air). After cooling, blank values ​​were measured separately, and multiple measurements were performed on the same low-sulfur antimony ore standard material (w(S) = 1.02%). The results are as follows: Figure 1 As shown.

[0052] Figure 1 The results showed that the blank value of the untreated crucible fluctuated between 0.003% and 0.0197%, with poor repeatability and an RSD of 66.80%. The blank value of the crucible pretreated at 1200℃ decreased to below 0.003% with good stability, and the RSD of the sample measurements decreased to within 19.3%, with the measured values ​​highly consistent with the standard values. Therefore, pretreatment of the crucible at 1200℃ before use can effectively remove moisture, trace sulfur, and other volatile impurities, significantly reducing the interference of the blank value on the determination of low sulfur content in antimony ore, and improving the accuracy and precision of the measurement results. The pretreated crucible should be used as soon as possible to avoid prolonged exposure to air and moisture absorption.

[0053] Example 3 The effect of the degree of dryness of the sample on the test results Free moisture in ore samples absorbs heat during high-frequency combustion, lowering the temperature inside the combustion furnace. This leads to incomplete combustion and conversion of sulfur in the sample. At the same time, the water vapor produced by the moisture interferes with the infrared absorption of SO2, resulting in lower measurement results and poor stability.

[0054] In this embodiment, the sulfur content of four antimony ore standard substances was determined after drying at 80℃ for 2 hours (this is consistent with the dry basis conditions used for standard substance determination). The results are as follows: Figures 2-5 As shown, comparing the measurement results of dried and untreated samples reveals that the measured data of the pretreated samples exhibit significantly better stability. This is mainly because the peak intensity of the infrared spectrum directly reflects the overall infrared absorption characteristics of the sample. Residual moisture in undried samples interferes with the infrared absorption signal, leading to larger fluctuations in the sulfur content measurement results. Based on the actual sulfur determination in antimony ore, drying at 80℃ effectively reduces the interference caused by moisture and improves the stability of the results; therefore, this temperature was used for sample drying pretreatment.

[0055] Example 4 The effect of sample weight on the measurement results The sample weight directly affects the complete combustion and conversion of sulfur in antimony ore. If the sample weight is too small, the sample will not be representative enough, which will easily lead to deviation in the measurement results. If the sample weight is too large, a large amount of antimony oxide melt will be generated during the combustion of antimony ore, which will coat the unburned sample and cause incomplete release of sulfur. At the same time, the excessive sample will increase the load on the combustion furnace, resulting in a decrease in furnace temperature and further affecting the conversion efficiency of sulfur.

[0056] In this experiment, the flux addition was fixed (0.5g pure iron filings + 1.5g tungsten granules + 0.5g tin granules). Four antimony ore standard substances were selected. Referring to Cai Dongfang et al.'s method of weighing samples based on varying sulfur content in antimony concentrate, different sample sizes of 5 mg, 10 mg, 20 mg, 50 mg, 70 mg, and 100 mg were used for measurement. The results are as follows: Figures 6-9 As shown.

[0057] Based on the results of measurements using antimony ore standard materials and reference antimony concentrate samples, and considering the impact of varying sulfur content on detection effectiveness, this embodiment establishes a graded weighing strategy for antimony ore samples with different sulfur contents. Specifically, when the sulfur content is in the range of 1.0% to 10%, a sample weight of 50 mg is used, balancing sample representativeness and combustion conversion efficiency, resulting in stable and reliable measurement results. When the sulfur content is approximately 1%, the weight is appropriately increased to 100 mg, effectively reducing relative error and improving measurement precision. When the sulfur content is in the range of 10% to 20%, a weight of 20 mg is used, avoiding problems such as excessive combustion and splashing, unstable sulfur release, and exceeding the instrument's measurement range due to excessive sample volume, ensuring accurate detection results. This graded weighing method is adaptable to the infrared carbon-sulfur analyzer detection requirements of antimony ore samples with different sulfur contents, balancing the accuracy, precision, and safety of the measurement results, and can provide a methodological reference for the determination of sulfur content in similar antimony sulfide, antimony oxide, and related ore samples.

[0058] Example 5 The effect of flux selection and addition amount on the test results Table 1. Effect of flux selection on sulfur determination results

[0059] The selection of flux is a key factor in ensuring the accuracy of sulfur content determination in antimony ore. Its core function is to lower the melting point of antimony sulfide melt, enhance sample permeability, and ensure complete sulfur release during combustion. This is because antimony sulfides in antimony ore have a low melting point and easily form a melt during combustion; improper flux selection can affect the detection results. Furthermore, the appropriate selection of flux directly determines the completeness of sulfur release during combustion. Therefore, this paper selects three fluxes—pure iron filings, tin granules, and tungsten granules—for related experiments.

[0060] The three fluxes each have their own characteristics: pure iron can improve the efficiency of induction heating and furnace temperature; tungsten particles form a loose skeleton to prevent the antimony molten material from encapsulating the sample; and tin particles improve the fluidity of the slag and promote the complete release of sulfur. The combined use of the three can solve the problems of antimony ore being difficult to ignite, prone to encapsulation, and slow to release sulfur.

[0061] This embodiment uses a single-factor experimental method based on the optimal sample weight for different content ranges. Experiments were conducted using pure iron, tin granules, and tungsten granules, both individually and in combination. The results show that when using tungsten granules alone, the sample cannot burn completely, and sulfur is not released completely. When tungsten granules are combined with pure iron, the sample still burns incompletely, and pits appear on the surface of the molten sample. When tungsten granules are combined with tin granules, the surface of the molten sample is not smooth enough, and cracks may appear when the amount used is small. Only when pure iron, tin granules, and tungsten granules are used in combination does the molten sample surface become smooth, the sample burn completely, sulfur is released completely, the peak elution rate is fast, and the detection results are stable.

[0062] To further test the influence of flux type and addition order on sulfur content determination results, this example selected three national standard materials (GBW07279, GBW07175, and GBW07176) with low, medium, and high sulfur contents, respectively. Based on the optimal sample weight for each content range, 0.5g of pure iron flux, 1.5g of tungsten granules, and 0.5g of tin granules were added, and experiments were conducted using different combinations. The experimental results are shown in Table 1. When the flux was added in the order of pure iron filings, tungsten granules, and tin granules, the sample combustion was most complete, the relative deviation between the measured and theoretical values ​​was smaller, and the detection effect was optimal. After determining the effects of flux type and addition order on sulfur content determination results in the above experiments, this experiment further investigates the effects of the dosage of three fluxes—pure iron, tungsten granules, and tin granules—on sulfur content determination results in antimony ore and related samples, thereby clarifying the optimal dosage of each flux and ensuring the accuracy of detection. During the experiment, it was found that the dosage of pure iron flux has a significant impact threshold: excessive dosage easily leads to splattering during sample combustion, while insufficient dosage results in incomplete combustion. Therefore, a systematic experiment is needed to determine its reasonable dosage.

[0063] This embodiment, based on the optimal sample weights for different content ranges in previous experiments, employs a single-factor experimental method to investigate the effects of the addition amounts of pure iron filings (0.2g, 0.5g, 1.0g), tungsten granules (1.0g, 1.5g, 2.0g), and tin granules (0.2g, 0.5g, 1.0g) on ​​the measurement results. Specifically, the steps are as follows: first, fix the pure iron flux at 0.5g and the tin granules at 0.5g; then, weigh out different gradients of tungsten granule flux. By analyzing the correlation coefficients between the measured and theoretical values, the effect of tungsten granule dosage on the measurement results is clarified. Similarly, using the same controlled variable method, the effects of different amounts of pure iron and tin granules on the measurement results are investigated.

[0064] The results are shown in Table 2: When the amount of pure iron filings added was 0.5g, the consistency between the measured results and the standard values ​​was the highest; when the amount of tungsten particles added was 1.0g, the skeleton support effect was insufficient, the sample was easily wrapped by the melt, and the sulfur was not completely released; when the amount added was 2.0g, the excessive tungsten particles would dilute the sample, resulting in the measured results of low sulfur samples being lower, and increasing the analysis cost; when the amount added was 1.5g, the loose skeleton formed could effectively prevent the melt from wrapping and ensure the complete release of sulfur.

[0065] In conclusion, the fluxing effect is optimal when the amount of pure iron filings added is 0.5g, the amount of tungsten particles added is 1.5g, and the amount of tin particles added is 0.5g, and the accuracy and precision of the measurement results are both at their best.

[0066] Table 2 Effect of flux addition on sulfur determination results

[0067] Example 6 Effect of analysis time on measurement results If the combustion time is too short, the sulfur in the antimony ore will not be completely burned into SO2, resulting in a lower measurement result; if the combustion time is too long, it has no practical detection significance, increases time and power costs, and may also lead to a decrease in the stability of the instrument detection system.

[0068] In this embodiment, other optimized parameters were kept constant, and combustion times of 30 s, 45 s, and 60 s were set to measure the results of three antimony ore standard materials. The results are shown in Table 3.

[0069] Table 3. Effect of combustion time on the measurement results

[0070] The results show that while the measured values ​​at a combustion time of 30 s are close to the standard values, the accuracy is poor. A combustion time of 60 s does not significantly improve upon 45 s and increases the analysis time. At a combustion time of 45 s, antimony ores with different sulfur contents are completely burned, resulting in accurate and stable measurements with high analytical efficiency. Therefore, 45 s is determined to be the optimal combustion time for determining the sulfur content of antimony ore.

[0071] The correctness and precision of the method Three national standard materials of antimony ore with different sulfur contents were selected according to the optimal experimental conditions obtained. Six parallel determinations were carried out according to the optimized method of this study. The relative error (RE) and relative standard deviation (RSD) of the determination results were calculated to verify the correctness and precision of the method.

[0072] The results showed that the average values ​​of all standard references were in high agreement with the standard values, with relative errors (RE) less than 1.96% and relative standard deviations (RSD) less than 1.35%. This indicates that the infrared absorption spectroscopy method for determining the sulfur content in antimony ore is accurate and reliable, meeting the quality requirements of geological and mineral laboratories for the determination of sulfur content in antimony ore.

[0073] In summary, this invention establishes an analytical method for determining sulfur content in antimony ore using a high-frequency infrared carbon-sulfur analyzer, based on the mineral characteristics of antimony ore. Through a systematic investigation of the effects of factors such as crucible blank, sample drying, sample weight, flux addition, and analysis time, the optimal determination conditions were determined: the crucible is pretreated at 1200℃, the sample is dried at 80℃, and samples are weighed according to sulfur content (50mg for 1.0%~10%, 100mg for ≈1%, and 20mg for 10%~20%). The flux used is a combination of 0.5g pure iron, 1.5g tungsten granules, and 0.5g tin granules, with a combustion time of 45s. The high-frequency infrared absorption method for determining sulfur content in antimony ore provided by this invention is accurate, stable, and rapid, suitable for batch detection of sulfur in antimony ore, and can provide technical support for geological exploration and mineral processing.

[0074] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for determining the sulfur content in antimony ore using high-frequency infrared absorption, characterized in that, Includes the following steps: S1. Establishing the working curve: Antimony ore standard material was measured using a high-frequency infrared carbon-sulfur analyzer, and the instrument infrared response value of the antimony ore standard material was recorded. With the sulfur content standard value of the antimony ore standard material as the abscissa (x) and the instrument infrared response value as the ordinate (y), a linear calibration curve was fitted using a multi-point calibration method to obtain the sulfur content determination working curve. The working curve is y = 0.9996x + 0.023, with a correlation coefficient R0. 2 =0.9995; S2. Sulfur content detection in antimony ore samples: Antimony ore samples were graded and weighed according to their sulfur content, and then dried to obtain antimony ore samples to be tested. The antimony ore sample to be tested and the flux are mixed and placed in a high-frequency infrared carbon-sulfur analyzer. The test program is started, and the sulfur content of the antimony ore sample is calculated and output according to the working curve. The flux is iron filings, tungsten granules, and tin granules; the mass ratio of the iron filings, tungsten granules, and tin granules is 0.48~0.52:1.4~1.6:0.48~0.

52. The graded sampling includes: antimony ore with a sulfur content of 1.0~10.0 wt%, with a sample weight of 50 mg; antimony ore with a sulfur content of ≈1.0 wt%, with a sample weight of 100 mg; and antimony ore with a sulfur content of 10.0~20.0 wt%, with a sample weight of 20 mg.

2. The method for determining the sulfur content in antimony ore according to claim 1, characterized in that, In step S2, the mixing is carried out in a crucible; the crucible is pretreated before use; the pretreatment temperature is 1180~1220℃.

3. The method for determining the sulfur content in antimony ore according to claim 1, characterized in that, The operating parameters of the high-frequency infrared carbon-sulfur analyzer are as follows: output power 3.4~3.6 kW; input current 19~21 A; analytical gas flow rate 4 L·min. -1 Oxygen flow rate is 1.5~2.0 L·min -1 The gas pressure is as follows: oxygen output pressure 0.6 MPa, oxygen input pressure 0.30~0.50 MPa, total oxygen pressure 0.18 MPa, and analytical pressure 0.08 MPa. The time parameters are: rinsing time 30 s, delay time 3 s, desorption time 60 s, and combustion time 40~50 s.

4. The method for determining the sulfur content in antimony ore according to claim 1, characterized in that, In step S2, the antimony ore sample to be tested and the flux are mixed by adding iron filings, tungsten particles and tin particles to the antimony ore sample in sequence without stirring.

5. The method for determining the sulfur content in antimony ore according to claim 1, characterized in that, The tungsten particles have a diameter of 0.380 mm; the tin particles have a diameter of 280~830 μm.

6. The method for determining the sulfur content in antimony ore according to claim 1, characterized in that, The particle size of the antimony ore sample is ≤200 mesh.

7. The method for determining the sulfur content in antimony ore according to claim 1, characterized in that, The total mass percentage of antimony oxides in the antimony ore sample was 5.0~70.0 wt%.

8. The method for determining the sulfur content in antimony ore according to claim 1, characterized in that, In step S2, the drying temperature is 60~80℃ and the time is 1~2h.